Nutraceuticals Obtained by SFE-CO2 from Cladodes of Two Opuntia ficus-indica (L.) Mill Wild in Calabria - Domenico Iacopetta; Noemi Baldino; Anna Caruso; Valentina Perri; Francesca Romana Lupi; Bruno de Cindio; Domenico Gabriele; Maria Stefania Sinicropi (Applied Sciences, 2021)
The aim of the present study was to evaluate the possibility to extract, by supercritical fluids, nutraceuticals as polyphenolic compounds, able in the prevention and in the treatment of a series of chronic-degenerative diseases, from plant matrices like the cactus pear. Supercritical fluid technology is an innovative method to extract nutraceuticals from natural matrices. This method offers numerous advantages that include the use of moderate temperatures, solvents with good transport properties (high diffusivity and low viscosity), and cheap and nontoxic fluids. Fresh cladodes from two different wild ecotypes of Opuntia ficus-indica (L.) Mill. were extracted both with methanol and with SFE-CO2 using different samples preparations, to maximize the % yields and the selectivity of extraction of polyphenols. The biggest contents of phenolics, evaluated by Folin-Ciocalteu assay, has been observed with the sample dehydrated of O. ficus-indica cultivar that shows, as well, the best yield % (m/m) of extraction with both methanol and SFE-CO2. Better results were obtained with the samples of O. ficus-indica cult. (OFI cult.), in spite of the O. ficus-indica s.l. (OFI s.l.); the two different ecotypes of OFI showed dissimilar phytochemicals profile. We noticed that the reduction of both quantity and quality of polyphenols was drastic with the increase of pressure at 250 bar; this shows that high pressures result in a loss of bioactive principles, like polyphenols. By changing the variables of extraction processes with SFE-CO2 and by varying the preventive treatments of the natural matrices, it was possible to increase the selectivity and the purity of the products. Thus, the optimization of this useful and green technique allowed us to increase the value of the Opuntia cladodes, a by-product very diffused in Calabria, which is an extraordinary source of nutraceuticals. These extracts could be used directly as functional foods or as starting material in the pharmaceutical, nutraceutical or cosmetic companies; they are safe and without any solvents traces and it is possible to obtain it in a few hours respect to the conventional extraction that requires longer extraction time.